2021
DOI: 10.1038/s41598-021-97502-1
|View full text |Cite
|
Sign up to set email alerts
|

In-house reverse transcriptase polymerase chain reaction for detection of SARS-CoV-2 with increased sensitivity

Abstract: As the COVID-19 infection continues to ravage the world, the advent of an efficient as well as the economization of the existing RT-PCR based detection assay essentially can become a blessing in these testing times and significantly help in the management of the pandemic. This study demonstrated an innovative and rapid corroboration of COVID-19 test based on innovative multiplex PCR. An assessment of optimal PCR conditions to simultaneously amplify the SARS-CoV-2 genes E, S and RdRp has been made by fast-conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Moreover, they can also retrieve information from the small sample volume. Microfluidic devices are used at the early stage of diagnosis as recent researchers have found that they can detect viruses (Kalita et al 2021 ). The genetic code that forms virus consists of an envelope of proteins and a lipid ligand.…”
Section: Diagnosis Of Sars-cov-2 Infestationmentioning
confidence: 99%
“…Moreover, they can also retrieve information from the small sample volume. Microfluidic devices are used at the early stage of diagnosis as recent researchers have found that they can detect viruses (Kalita et al 2021 ). The genetic code that forms virus consists of an envelope of proteins and a lipid ligand.…”
Section: Diagnosis Of Sars-cov-2 Infestationmentioning
confidence: 99%
“…One advantage of these tests, as opposed to RT-PCR with fluorogenic probes, is that they allow for assessment of the amplification specificity by simply examining the amplicon melting curves at the end of the PCR [18]. While most SYBR Green-based RT-PCR protocols have been established for use with RNA isolated from naso-or oropharyngeal specimens [11,16,[19][20][21][22][23][24][25][26][27], there is promising evidence for the use of saliva samples with this type of tests. Ganguly et al amplified synthetic SARS-CoV-2 RNA spiked into saliva specimens from healthy donors [28].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%